2010
DOI: 10.1055/s-0030-1253422
|View full text |Cite
|
Sign up to set email alerts
|

Leptin, Soluble Leptin Receptors, Free Leptin Index, and Their Relationship with Insulin Resistance and BMI: High Normal BMI is the Threshold for Serum Leptin Increase in Humans

Abstract: Leptin binds to the soluble form of its receptor (sOB-R). Leptin and sOB-R balance (free leptin index, FLI) reflect leptin activity. Leptin correlates with obesity and insulin resistance, but it remains uncertain whether sOB-R and FLI also do the same. Therefore, the aim of this study was to measure serum leptin, sOB-R, and FLI, and evaluate their associations with BMI and insulin resistance. We studied 145 obese and 49 nonobese humans. Obesity was defined according to WHO (BMI >30 kg/m (2)). Results are given… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 16 publications
0
45
2
1
Order By: Relevance
“…Our data also did not support the role of FLI, which is considered to better reflect leptin activity (43,44). These results are in contrast to the evidence from 2 previous prospective studies, which reported that leptin is associated to risk of CRC independently of BMI.…”
Section: Discussioncontrasting
confidence: 99%
“…Our data also did not support the role of FLI, which is considered to better reflect leptin activity (43,44). These results are in contrast to the evidence from 2 previous prospective studies, which reported that leptin is associated to risk of CRC independently of BMI.…”
Section: Discussioncontrasting
confidence: 99%
“…The FLI has been developed and suggested as a marker of the presumed free leptin concentrations [19,20,29]. Not surprisingly, FLI exhibited tracking, as did its constituents, leptin and SLR.…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of leptin, an adipocyte-derived adipokine that classically plays a crucial role in regulating appetite and energy balance, are strongly correlated with body fat content and markedly elevated in obese individuals (2, 3) as well as in breast, ovarian, and endometrial cancer patients (4, 5). The women’s health initiative studies have identified obesity as a major breast cancer risk factor for postmenopausal women who had never taken hormone replacement therapy (6).…”
Section: Introductionmentioning
confidence: 99%